Revisiting the genotypes of Theileria equi based on the V4 hypervariable region of the 18S rRNA gene - Nehra, Anil Kumar; Kumari, Ansu; Moudgil, Aman Dev; Vohra, Sukhdeep (Frontiers in Veterinary Science, 2024)
The present study was aimed to revisit the phylogeny, genetic diversity and geographical distribution of Theileria equi based on the nucleotide sequences of the V4 hypervariable region of the 18S rRNA gene available in the nucleotide databases. Out of 14792 nucleotide sequences of T. equi available in the GenBankTM, only 736 sequences of T. equi containing the complete V4 hypervariable region of the 18S rRNA gene (>207 bp) were used in multiple sequence alignment. The phylogenetic tree placed all the sequences into four distinct clades with high bootstrap values which were designated as T. equi clades/ genotypes A, B, C and D. Our results indicated that the genotype B of Nagore et al. (2004) and genotype E of Qablan et al. (2012b) together formed the clade B with a high bootstrap value (95%). Furthermore, all the genotypes probably originated from clade B, which was the most dominant genotype (52.85%) followed by clades A (27.58%), and C (9.78%) and D (9.78%). Genotype C manifested a comparatively higher genetic diversity (91.0-100% identity) followed by genotypes A (93.2-99.5%), and B and D (95.7-100%). The alignment report of the consensus nucleotide sequences of the V4 hypervariable region of the 18S rRNA gene of four T. equi genotypes (A-D) revealed significant variations in one region, between nucleotide positions 113-183, and 41 molecular signatures were recognized. As far as geographical distribution is concerned, genotypes A and C exhibited far-extending geographical distribution involving 31 and 13 countries of the Asian, African, European, North American and South American continents, respectively. On the contrary, the genotypes B and D exemplified limited distribution with confinement to 21 and 12 countries of Asian, African and European continents, respectively. Interestingly, genotypes A and C have been reported from only two continents, viz., North and South America. It was observed that genotypes A and C, and B and D exhibit similar geographical distribution. In conclusion, the present study indicated the presence of only four previously described T. equi genotypes (A, B, C and D) after performing the molecular analyses of all available nucleotide sequences of T. equi isolates in the GenBankTM.